Sliding mode control design of a ship steering autopilot with input saturation. (3rd May 2017) - Ejaz, Muhammad; Chen, Mou
In this article, a sliding mode control scheme for the autopilot system of a ship is presented, which also incorporates actuator saturation. Under the designed controller, the actuator doesn't enter its saturation mode. Meanwhile, the stability of the closed-loop system can be guaranteed for the ship with input saturation. Fuzzy logic is used to handle gain to avoid the chattering effect, and it is compared with saturation function. The control system for the mathematical model of a scale replica of an "Esso Osaka" tanker is simulated in time domain for the effectiveness of the controller. The simulation results show that the proposed controller is more efficient as compared to the traditional and saturation function methods.